Hubungan Antara Minat dengan Keterampilan Dasar Siswa yang Mengikuti Ekstrakurikuler Bola Voli SMP N 6 Banda Aceh - Aji Afrilian Wali (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research aims to determine the relationship between interest and basic volleyball skills of students who take part in extracurricular volleyball at SMP Negeri 6 Banda Aceh in 2023. The research design used is a correlational design. The method used in this research is a survey method with research questionnaires and skills tests. The variable that is the independent variable is the interest of students who take part in extracurricular volleyball at SMP Negeri 6 Banda Aceh towards learning volleyball skills which is seen from 3 factors, namely interest/enjoyment, attention and activity. Meanwhile, the attachment variable is basic volleyball skills. The subjects of this research were students who took part in extracurricular volleyball at SMP Negeri 6 Banda Aceh, totaling 20 students. The data analysis technique was carried out using simple linear regression analysis and product moment correlation analysis. The results of the research show that there is a very strong and significant positive relationship between interest and students' basic volleyball skills with a correlation value of 0.842 and the influence of the interest variable on basic volleyball skills is 70.9%. Thus, it can be said that the higher the student's interest in extracurricular volleyball learning, the better the students' basic volleyball skills will be.